Factors lead to customer loyalty in prepaid mobile services - Shamsudin, Mohd Farid; Mohd Noor, Nor Azila; Abu Hassim, Affendy; Hussain, Hafezali Iqbal; Salem, Milad Abdelnabi; Hasim, Muhammad Asyraf (2015)
This research focuses on the factors of customer loyalty in the service industry particularly in telecommunication industry and aims to solve the issues related to the prepaid mobile services. The research was conducted to evaluate the relationship between service quality, customer perceived value and customer trust against customer loyalty.Surveys are conducted using survey responses from a sample of 398 respondents. The result of this research indicates that there is a positive relationship between customer support service, service reliability, emotional value and customer trust with customer loyalty. The results are also compared with previous earlier findings and implications for future research are discussed. Suggestion was made to conduct future research using longitudinal evidence by evaluating the relationship among and in-between variables towards customer loyalty in service industry.